2011
DOI: 10.1007/s10935-011-0239-7
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Drug Resistance Skills of Youth in Guanajuato, Mexico

Abstract: Research is limited or absent on Mexican adolescents’ exposure to substance offers, ways of dealing with these offers, and possible gender differences in responses to offers. Extending U.S.-based research, this study examines how youth living in the Mexican state of Guanajuato employ the four drug resistance strategies—refuse, explain, avoid, and leave—that are part of the Keepin’ It REAL evidence-based drug prevention intervention. The analysis uses cross-sectional survey data from 702 students enrolled in ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 35 publications
0
14
1
Order By: Relevance
“…Social skills training compared with pharmacotherapy and psychotherapy in the treatment of unipolar depression. which is designed to equip youth in middle school with a repertoire of skills to resist substance use offers (Gosin, Marsiglia, & Hecht, 2003 (Alberts, Miller-Rassulo, & Hecht, 1991;Kulis, Marsiglia, Castillo, Becerra, & Nieri, 2008;Kulis, Marsiglia, Ayers, Calderón-Tena, & Nuño-Gutierrez, 2011;Marsiglia, Kulis, Martinez Rodriguez, Becerra, & Castillo, 2009). The L2W curriculum is designed to reflect the social contexts in which UAI youth are exposed to substances and culturally influenced ways of responding to offers to use them.…”
Section: Discussionmentioning
confidence: 99%
“…Social skills training compared with pharmacotherapy and psychotherapy in the treatment of unipolar depression. which is designed to equip youth in middle school with a repertoire of skills to resist substance use offers (Gosin, Marsiglia, & Hecht, 2003 (Alberts, Miller-Rassulo, & Hecht, 1991;Kulis, Marsiglia, Castillo, Becerra, & Nieri, 2008;Kulis, Marsiglia, Ayers, Calderón-Tena, & Nuño-Gutierrez, 2011;Marsiglia, Kulis, Martinez Rodriguez, Becerra, & Castillo, 2009). The L2W curriculum is designed to reflect the social contexts in which UAI youth are exposed to substances and culturally influenced ways of responding to offers to use them.…”
Section: Discussionmentioning
confidence: 99%
“…A similar adaptational process has occurred with another drug prevention program ( keepin’ it REAL ), which is an evidence-based, culturally grounded drug prevention program for Mexican/Mexican American youth of the southwest United States. keepin’ it REAL is in various stages of adaptation to related youth populations in Monterrey and Guanajuato, Mexico (Kulis, Marsiglia, Ayers, Calderón-Tena, & Nuño-Gutierrez, 2011; Marsiglia, Kulis, Martinez Rodriguez, Becerra, & Castillo, 2009), and in Galicia, Spain (Marsiglia, Kulis, Luengo, Nieri, & Villar, 2008). Similarly, a fully conceived video-based prevention program for rural Hawaiian youth could be adapted to related youth populations in other Pacific islands or regions.…”
Section: Discussionmentioning
confidence: 99%
“…In alignment with these norms, older adolescents in Mexico report using the REAL drug resistance strategies in gender-specific ways. Males use the strategies more often than females and their use of the strategies is more strongly associated with lower levels of substance use than for females (Kulis et al, 2011, 2012). When keepin’ it REAL was implemented in Mexico, the short-term effects also demonstrated gender differences, but in a different direction.…”
Section: Introductionmentioning
confidence: 98%
“…We selected keepin’ it REAL because the original curriculum reflects the experiences of Mexican–American youth in a region bordering Mexico and because it uses an interactive approach to primary prevention that is a highly effective format with preadolescents (Kulis et al, 2005; Marsiglia & Hecht, 2005). Although the cultural context of Mexico differs from that of Mexican–American youth living in the US, preliminary studies indicated that the core elements of the keepin’ it REAL intervention, including the drug resistance strategies it teaches, were relevant to Mexican youth from different regions (Kulis, Marsiglia, Ayers, Booth, & Nuño-Gutiérrez, 2012; Kulis, Marsiglia, Ayers, Calderón-Tena, & Nuño-Gutierrez 2011; Kulis, Marsiglia, Castillo, Bercerra, & Nieri, 2008; Marsiglia, Kulis, Martínez-Rodríguez, Becerra, & Castillo, 2009). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation